2023
DOI: 10.1097/pgp.0000000000000952
|View full text |Cite
|
Sign up to set email alerts
|

Atypical Endometriosis: Comprehensive Characterization of Clinicopathologic, Immunohistochemical, and Molecular Features

Abstract: Atypical endometriosis (A-EMS), defined by cytologic atypia and/or crowded glands resembling endometrial intraepithelial neoplasia, remains poorly understood. We aimed to refine the morphologic, immunohistochemical, and molecular features of A-EMS in an institutional series. Cases were identified through a structured search and reviewed by 2 pathologists. Immunohistochemistry and comprehensive sequencing using a panel 447-gene coverage were performed in suitable cases. A-EMS with synchronous and/or subsequent … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(14 citation statements)
references
References 12 publications
0
14
0
Order By: Relevance
“…Finally, 134 articles were considered eligible for the systematic review; of these, 118 were also excluded for the absence of reported outcomes related to AE or the design of the study not in line with the inclusion criteria. Overall, 16 studies were finally selected for this review, 14 retrospective studies [ 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 ], and 2 prospective studies [ 27 , 28 ]. The selection process is summarized in the PRISMA flowchart in Figure 1 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, 134 articles were considered eligible for the systematic review; of these, 118 were also excluded for the absence of reported outcomes related to AE or the design of the study not in line with the inclusion criteria. Overall, 16 studies were finally selected for this review, 14 retrospective studies [ 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 ], and 2 prospective studies [ 27 , 28 ]. The selection process is summarized in the PRISMA flowchart in Figure 1 .…”
Section: Resultsmentioning
confidence: 99%
“…A total of 6 articles evaluated the prevalence and the histopathology of atypical endometriosis ( Table 1 ). The general prevalence of AE in patients with endometriosis was found to range from <1% [ 13 ] to 5.8% [ 17 ], while in the case of EAOC, the prevalence was significantly higher, ranging from 22.8 to 34.6% [ 15 , 27 ]. For what concerns the histologic definition of AE, some authors discerned between cellular atypia and architectural atypia.…”
Section: Resultsmentioning
confidence: 99%
“…Also, sequencing of deep endometriotic lesions has revealed known somatic cancer driver mutations in 26% of the samples, including mutations in ARID1A and PIK3CA [ 55 ]. In addition, rare, atypical cytological features harboring endometriotic lesions have been shown to increase the risk for synchronous or subsequent borderline or carcinoma tumors, with prevalence ranging from 12,2 to 25% in the cohorts [ 56 , 57 ]. Despite cancer-associated mutations being relatively common in non-cancerous endometrial tissue, and malignant transformation is rare, accumulating evidence indicate endometriotic lesions as precursors for malignancy.…”
Section: Discussionmentioning
confidence: 99%
“…Due to these histologic findings and subsequent molecular data suggesting a clonal relationship between atypical endometriosis and EAOC (discussed in more detail below), atypical endometriosis has been suggested as the putative precursor of EAOC, but nevertheless is not identified in all cases of EAOC [ 48 ]. Wepy et al recently reviewed and analyzed over 4500 cases of endometriosis and identified 36 cases of atypical endometriosis [ 49 ]. Of the 36 cases, 9 had associated endometrioid, sero-mucinous, and clear-cell tumors (borderline and invasive).…”
Section: Methodsmentioning
confidence: 99%
“…Sequencing showed pathogenic variants in five of six cases analyzed, involving mutations in ATM , BRCA2 , KRAS , AKT , CTNNB1 , PTEN , and ARID1A . TP53 was wild-type in all cases, and mismatch repair was intact [ 49 ]. Interestingly, proteomic studies have suggested that ovarian endometrioid carcinoma arises from the secretory cells of endometriosis, while clear-cell carcinomas arise from ciliated cells [ 50 ].…”
Section: Methodsmentioning
confidence: 99%